2014
DOI: 10.1371/journal.pone.0102284
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Contribute to Excess Serum BAFF Levels and Promote CD4+ T Cell and B Cell Responses in Lupus-Prone Mice

Abstract: Despite increased frequencies of neutrophils found in autoimmune diseases such as systemic lupus erythematosus (SLE), how they contribute to disease pathogenesis and the mechanisms that affect the accumulation of neutrophils are poorly understood. The aim of this study was to identify factors in autoantibody-mediated autoimmunity that controls the accumulation of spleen resident neutrophils and to determine whether neutrophils contribute to abnormal B cell responses. Increased levels of the cytokine BAFF have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 51 publications
5
51
0
2
Order By: Relevance
“…Neutrophils localized to the RP and MZ, a distribution that was clearly distinguishable from autoinflammatory processes where neutrophils can be located in the T-cell zone (53). Depletion of neutrophils in Em-Tcl1 mice delayed leukemia proliferation associated with the upregulation of the cell-cycle inhibitor Egr1 and the differentiation factor Egr2 (25,26).…”
Section: Discussionmentioning
confidence: 94%
“…Neutrophils localized to the RP and MZ, a distribution that was clearly distinguishable from autoinflammatory processes where neutrophils can be located in the T-cell zone (53). Depletion of neutrophils in Em-Tcl1 mice delayed leukemia proliferation associated with the upregulation of the cell-cycle inhibitor Egr1 and the differentiation factor Egr2 (25,26).…”
Section: Discussionmentioning
confidence: 94%
“…Increases in neutrophil infiltration have been shown to enhance IFN-γ production through the production of B-cell activating factor (Coquery et al, 2014). While changes in IFN-γ production were not observed at 24 h in this study, it is possible that this cytokine is latently activated after neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Tnfrsf17À/À mice treated with the inflammatory agent pristine showed TFH cell accumulation, indicating that BCMA reduces the expansion of TFH cells and the development of autoimmunity. Coquery and his team reported that in lupus-prone mice with BCMA deficiency, the activation status and neutrophil accumulation were found to be increased significantly in the spleen tissues [46].…”
Section: Bcmamentioning
confidence: 99%